PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Dede Ajay Hardiansyah; Lunamaya Apriyani; Jamilah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Indonesian is a means of communication that characterises the Indonesian nation and is used as the national language. Indonesian language lessons are one of the subjects that must be taught in elementary school. This is one of the reasons why Indonesian language lessons must be taught at all levels of education, especially in elementary school/Islamic elementary school because it is the basis of all learning. If the teacher understands the purpose of this subject, it will have an impact on learning activities that lead to students being able to communicate through Indonesian. Indonesian language learning is directed by the teacher to enable students to understand and use Indonesian eflectively and efficiently, both orally and in writing. This article discusses several strategies that can be used by teachers in the Indonesian language learning process to improve students' learning outcomes in four languages. The strategies found in this paper are strategies that have been explored from various literature sources. One aspect that greatly determines learning success is the use of learning strategies. Therefore, teachers should be able to choose and use strategies that are in line with the learning objectives to be achieved